Genetic diversity of Salvia tomentosa Miller (Lamiaceae) species using Touch-down Directed Amplification of Minisatellite DNA (Td-DAMD) molecular markers - Saleh, Basel (Acta Biologica Szegediensis, 2020)
Salvia tomentosa Miller (Lamiaceae) a Mediterranean species has an important role in various pharmacological applications. To reveal genetic relationships among S. tomentosa natural populations, 35 samples were collected from different regions of Syria. Touch-down Directed Amplification of Minisatellite DNA (Td-DAMD) markers have been investigated for this goal. Td-DAMD assay produced 158 total bands of which 131 (82.911%) were polymorphic with a mean polymorphic information content (PIC) value of 0.264 and a mean marker index (MI) value of 2.269. Clustering profile based on TdDAMD data showed that samples were grouped into two main clusters; the first cluster included Lattakia samples which split into two subclusters regardless their altitudes over the sea level. Whereas, the second cluster included Tartous and Hama samples. Td-DAMD assay successfully discriminate among the tested 35 samples belonged to the S. tomentosa natural population.